Study on the effect of health education on dietotherapy and medicated diet for the community-dwelling elderly in Nanning city (南宁市社区老年人食疗药膳健康教育效果研究) - LIN Xiaomin (林小敏); QIN Yi (覃毅); LING Xingping (凌鑫萍); HUO Lijuan (霍李娟); CHEN Yu (陈裕) (Association of Integrative Nursing, 2021)
Objective To understand the cognition and demand of the community-dwelling elderly for dietotherapy and medicated diet, analyze the effect of health education on dietotherapy and medicated diet knowledge, and provide basis for further health education of dietotherapy and medicated diet. Methods By using the methods of cluster random sampling, a survey was conducted on the knowledge and needs of dietotherapy and medicated diet among 81 elderly people from several communities of Nanning. Results The average total score of cognitive assessment was (12. 93±2. 82)points before implementation of health education, which was lower than (18. 83±2. 85)points after implementation of health education(P＜0. 01). The community-dwelling elderly had a broad range of needs for knowledge about dietotherapy and medicated diet. Conclusion There is a high demand for dietotherapy and medicated diet among the community-dwelling elderly. Health education is an effective tool to improve the community-dwelling elderly people's awareness and skills of conducting dietotherapy and medicated diet, thereby improving the quality of life. (目的 了解社区老年人对食疗药膳的认知程度及需求情况, 分析开展食疗药膳知识健康教育的效果, 为进一步开展社区老年人食疗药膳知识的健康教育提供依据。方法 采取整群随机抽样法, 对广西南宁市81名社区老年人食疗药膳知识的认知及需求调查, 并对其进行健康教育。结果 实施健康教育前, 社区老年人食疗药膳认知评价总分为(12. 93±2. 82)分, 实施后总分为(18. 83±2. 85)分, 差异有统计学意义(P＜0. 01)。社区老年人对食疗药膳知识的需求是多方面的。结论 社区老年人对食疗药膳需求程度较高, 实施健康教育可以提高老年人对食疗药膳知识的认知程度, 让社区老年人懂得运用食疗药膳促进健康生活。)